ENTERAL NUTRITION AND BURN WOUND RECOVERY OF PAEDIATRIC PATIENTS: A CASE OF KIRUDDU NATIONAL REFERRAL HOSPITAL - Susan Nassiwa; Fred Kigozi; Jane Frank Nalubega (Student's Journal of Health Research, 2023)
Background:  The study aimed at finding the relationship between normal oral nutrition, use of liquid supplements, tube feeding and burn wound recovery of pediatric patients at Kiruddu National Referral Hospital. Methodology: A descriptive  cross-sectional study  design  conducted  among  caretakers  of pediatric  burn  patients  using  the  prospective  sampling  method.  Socio- demographic factors, medical history, dietary history, 24 hr. recall and biochemical analysis were assessed. Results: 45 caretakers of pediatric burn patients (mean age = 4.08) were studied. The patients sustained between 02-55% TBSA burns. Majority burns occurred for children aged between 0-5. With (71.1%) largest burns caused by scalds, (20%) flames and (8.9%) chemicals. Overall, 73.3% of pediatric patients placed on normal oral nutrition while 26.7% tube feeding. None of the pediatric patients under study received a liquid supplement. Data analysis of enteral nutrition feeding routes and nutrition outcomes was conducted using the chi square. The results showed that there is a significant and positive relationship between normal oral nutrition, tube feeding and white blood cells (p= 0.005), red blood cells (p= 0.001), hemoglobin (p= 0.000), platelets (p= 0.000), creatinine (p= 0.000), urea (p= 0.000), sodium (p= 0.000), potassium (p= 0.000), chloride (p= 0.000) and albumin (p= 0.002,). The blood cells, protein and biochemical parameters are indicative of wound healing. With linear regression the relationship between normal oral nutrition, tube feeding and albumin was found to be of no significance (p=0.553). Conclusions: The study illustrated a significant relationship between normal oral nutrition, burn wound recovery and a positive relationship between tube feeding and burn wound recovery of pediatric burn patients at Kiruddu National Referral Hospital. Recommendations: There is need to carry out a biochemical analysis test that includes transferrin, transthyretin, magnesium, zinc and copper as these tests can help in determining the nutrition status of the patients.